Biosynthesis, Deficiency, and Supplementation of Coenzyme Q - Carmine Staiano; Laura García-Corzo; David Mantle; Nadia Turton; Lauren E. Millichap; Gloria Brea-Calvo; Iain Hargreaves (MDPI AG, 2023)
Originally identified as a key component of the mitochondrial respiratory chain, Coenzyme Q (CoQ or CoQ10 for human tissues) has recently been revealed to be essential for many different redox processes, not only in the mitochondria, but elsewhere within other cellular membrane types. Cells rely on endogenous CoQ biosynthesis, and defects in this still-not-completely understood pathway result in primary CoQ deficiencies, a group of conditions biochemically characterised by decreased tissue CoQ levels, which in turn are linked to functional defects. Secondary CoQ deficiencies may result from a wide variety of cellular dysfunctions not directly linked to primary synthesis. In this article, we review the current knowledge on CoQ biosynthesis, the defects leading to diminished CoQ10 levels in human tissues and their associated clinical manifestations.